Paramedic educational programs maintain entry level competency throughout the COVID‐19 pandemic - Shea L. vanden Bergh; Lakeshia T. Logan; Jonathan R. Powell; Christopher B. Gage; Kathryn R. Crawford; Lisa Collard; Michael G. Miller; Ashish R. Panchal (Journal of the American College of Emergency Physicians Open)
Abstract Objective The COVID‐19 pandemic required unprecedented changes to emergency medical services (EMS) educational frameworks in the United States. It is unclear if pandemic‐related changes impacted paramedic educational outcomes. We aimed to evaluate curricular and performance changes resulting from the initial COVID‐19 pandemic on paramedic educational programs. Methods We performed a retrospective cross‐sectional evaluation of paramedic educational programs in 2019 and 2020 using the Committee on Accreditation of Educational Programs for the Emergency Medical Services Professions annual reports. These reports contain detailed program components and measures of program success. We included programs reporting at least one graduate in the study period. Descriptive statistics (proportions [%], median [interquartile range, IQR]) were calculated for paramedic program characteristics in 2019 and 2020, as well as pandemic specific curriculum changes. Wilcoxon rank‐sum and Fisher's exact tests were used to evaluate differences in characteristics by year. Results The number of paramedic educational programs in our population decreased from 640 programs in 2019 to 612 in 2020, with a statistically significant decrease in clinical hours (2019: 219 [IQR 168‒272]; 2020: 200.5 [IQR 157‒261]). There was no difference in first or third‐attempt certification examination success between years. Temporary shutdown was experienced in 34% of programs (duration: 3 weeks [2‒7]) and 72% of required curricular changes. Curricular changes commonly included decreased in‐person education (86%), traditional classroom lectures (78%), number of clinical sites (78%), and increased online didactic education (92%). Only 20% of programs decreased laboratory simulation or total training hours. Conclusion During the pandemic, paramedic educational programs changed educational delivery with no observed differences on overall program performance. Identifying key curricular changes and best practices for implementation may be necessary to better optimize future educational delivery.